The Organoleptic Quality Analysis of Functional Lemon Juice Drinks with Different Concentrations of Lemongrass: Analisis Mutu Organoleptik Minuman Fungsional Sari Lemon dengan Penambahan Konsentrasi Serai yang Berbeda - Dwi Marseva, Amalia; Sumarlina, Sumarlina; Napitupulu, Tia Sofiani; Nadhirah, Aulia (Politeknik Negeri Jember, 2026)
Teaching Factory (TeFa) of Innovation Garden is one of the TeFa’s at the Politeknik Negeri Jember which has consistently produced various agricultural products, one of which is local lemons. However, the consistency of local lemon production at the TeFa of Innovation Garden Polije is not in line with the revenue generation which tends to be lower than other products. One effort that can be made is to optimize post-harvest handling by diversifying lemon fruit products into functional lemon juice drink products. This research aims to create the best formulation of lemon juice drinks with the addition of honey at various concentrations, namely 0%, 1.5%, 2%, 2.5%, and 3%. The formula was then organoleptically tested based on the criteria of color, aroma, taste, and overall acceptability. The data obtained were analyzed using the ANOVA test and continued with the DMRT test at the 5% level. The results showed that the formulation of the honey lemon juice drink had been successfully carried out. The concentration of honey had a significant effect on the organoleptic test results for the criteria of color, aroma, and taste, but had no significant effect on the overall acceptance criteria. The best formula based on the percentage distribution of respondents' favorite levels was obtained from treatment with a honey concentration of 2.5% (SLM25), namely 45.71% with organoleptic test results on color criteria of 2.30 ± 1.05, the aroma of 2.97 ± 0 .96, the taste was 3.43 ± 0.87, and overall acceptability was 4.24 ± 0.76.